Lithium battery diaphragm with gradient pore structure and preparation method thereof
By using layered coating technology on lithium battery separators to construct a porous alumina coating with gradient pore structures, the shortcomings of the existing separators in terms of ionic conductivity and liquid absorption retention are solved, and higher conductivity and better mechanical properties are achieved.
Patent Information
- Application Number
- CN202411863330.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-17
AI Technical Summary
The existing lithium battery separators have shortcomings in improving ionic conductivity and liquid retention rate, which is difficult to meet the high requirements of modern electronic equipment for energy density and charging speed.
Using layered coating technology, a slurry containing large porous alumina is first coated on one side of the base film, and then a slurry containing small porous alumina is coated to construct a porous alumina coating with a gradient pore structure.
Through the design of the gradient pore structure, the ionic conductivity, liquid absorption and liquid retention rate of the lithium battery separator are effectively improved, while reducing the shrinkage rate, enhancing the mechanical strength and heat resistance.
Smart Images

Figure BDA0005193704940000051 
Figure BDA0005193704940000061 
Figure BDA0005193704940000071
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery separators, and in particular relates to a lithium battery separator with a gradient pore structure and a preparation method thereof. Background Art
[0002] As an indispensable core component in the battery structure, the lithium battery separator undertakes a vital dual task: on the one hand, it ensures the physical separation between the positive and negative electrodes of the battery, effectively preventing the occurrence of short-circuit accidents, and building a solid defense line for the safe operation of the battery; on the other hand, it also plays the role of a lithium ion transmission channel, allowing lithium ions to shuttle back and forth smoothly during the charging and discharging process, thereby realizing the battery's energy storage and release functions. Therefore, improving the ionic conductivity of the separator has become the key to optimizing the overall performance of lithium batteries and promoting their technological progress. This research field has naturally become a frontier in materials science exploration.
[0003] With the increasing popularity and rapid development of modern electronic devices, people have put forward higher and higher requirements for the energy density and charging speed of batteries. In this context, how to effectively improve the ion transmission efficiency and liquid retention capacity of lithium battery separators is particularly urgent and important. This not only requires researchers to continuously explore new ideas and methods in the design and synthesis of materials, but also requires in-depth research and innovation in the fields of microstructure regulation and surface modification technology, in order to develop a new type of separator material with better comprehensive performance.
[0004] In summary, it is undoubtedly of great significance to carry out in-depth and meticulous scientific research and technological innovation around the core issue of how to efficiently improve the ionic conductivity and liquid absorption and retention rate of lithium battery separators. This will not only strongly promote the development of high-performance lithium batteries, but also provide solid support and guarantee for meeting the high standards required by future energy storage systems. Therefore, the exploration and research work in this field undoubtedly has immeasurable value and potential. Summary of the invention
[0005] In view of the deficiencies of the prior art, an object of the present invention is to provide a lithium battery separator with a gradient pore structure.
[0006] Another object of the present invention is to provide a method for preparing the above-mentioned lithium battery separator with a gradient pore structure, wherein the preparation method adopts layered coating, wherein a slurry containing large-pore porous alumina is first coated on one side of the base membrane to serve as a bottom layer, and then a slurry containing small-pore porous alumina is coated on the bottom layer containing large-pore porous alumina to construct a porous alumina coating with a gradient pore structure.
[0007] The purpose of the present invention is achieved through the following technical solutions.
[0008] A lithium battery separator with a gradient pore structure is a layered structure, which includes: a base film, a first coating and a second coating, the first coating and the second coating are located on the same side of the base film, the first coating is connected to one side of the base film, the second coating is connected to the first coating, the porosity of the first coating is 40-50%, the porosity of the second coating is 30-40%, the first coating includes: large-pore porous alumina, the second coating includes: small-pore porous alumina, and the ratio of the large-pore porous alumina in the first coating to the small-pore porous alumina in the second coating is (10-30): (10-30) by mass.
[0009] In the above technical solution, the particle size of the large-pore porous alumina is D50=0.6-0.8 μm, D90=1.4-1.6 μm, the pore size of the large-pore porous alumina is 50-100 nm, and the specific surface area of the large-pore porous alumina is 30-40 m 2 / g.
[0010] In the above technical solution, the particle size of the small-pore porous alumina is D50=0.3-0.5 μm, D90=0.8-1.2 μm, the pore size of the small-pore porous alumina is 10-20 nm, and the specific surface area of the small-pore porous alumina is 10-20 m 2 / g.
[0011] In the above technical solution, the thickness of the first coating layer is 1 to 2.5 μm, and the thickness of the second coating layer is 1 to 2.5 μm.
[0012] In the above technical solution, the first coating also includes: acrylate copolymer and ammonium polyacrylate. The ratio of the large-pore porous alumina, the acrylate copolymer in the first coating and the ammonium polyacrylate in the first coating is (10-30): (1-4): (0.5-1), preferably (25-30): (1.8-4): (0.9-1).
[0013] In the above technical solution, the second coating also includes: acrylate copolymer and ammonium polyacrylate. The ratio of the small-pore porous alumina, the acrylate copolymer in the second coating and the ammonium polyacrylate in the second coating is (10-30): (1-4): (0.5-1), preferably (25-30): (1.8-4): (0.9-1), by weight.
[0014] The preparation method of the above-mentioned lithium battery separator with a gradient pore structure includes: applying a first slurry containing large-pore porous alumina on a base membrane, drying, and obtaining a first coating on the base membrane, applying a second slurry containing small-pore porous alumina on the surface of the first coating, drying, and obtaining a second coating on the first coating, thereby obtaining a lithium battery separator with a gradient pore structure.
[0015] In the above technical solution, the drying temperature is 30-50° C., and the drying time is 1-4 minutes.
[0016] In the above technical solution, the coating speed is 10 to 30 m / min.
[0017] In the above technical solution, the first slurry includes: large-pore porous alumina, water, an adhesive and a dispersant. In terms of mass fractions, the ratio of large-pore porous alumina, water in the first slurry, the adhesive in the first slurry and the dispersant in the first slurry is (10-30): (50-90): (5-10): (0.5-1).
[0018] In the above technical solution, the ratio of large-pore porous alumina, water in the first slurry, adhesive in the first slurry and dispersant in the first slurry is preferably (25-30): (50-70): (9-10): (0.9-1) by mass.
[0019] In the above technical solution, the second slurry includes: small-pore porous alumina, water, adhesive and dispersant. In terms of mass percentage, the ratio of small-pore porous alumina, water in the second slurry, adhesive in the second slurry and dispersant in the second slurry is (10-30): (50-90): (5-10): (0.5-1).
[0020] In the above technical solution, the ratio of small-pore porous alumina, water in the second slurry, adhesive in the second slurry and dispersant in the second slurry is preferably (25-30): (50-70): (9-10): (0.9-1) by mass.
[0021] In the above technical solution, the method for preparing the first slurry includes: mixing large-pore porous alumina, water, an adhesive and a dispersant until they are uniform to obtain the first slurry.
[0022] In the above technical solution, the method for preparing the second slurry includes: mixing small-pore porous alumina, water, an adhesive and a dispersant until they are uniform to obtain the second slurry.
[0023] In the above technical solution, the method for preparing the first slurry specifically comprises the following steps:
[0024] Step 1, mixing large-pore porous alumina, water and a dispersant, and stirring at a rotation speed of 1000 to 3000 r / min and a revolution speed of 30 to 50 r / min for 10 to 30 minutes until uniform, to obtain a first solution;
[0025] Step 2: Mix the first solution and the adhesive, stir and ultrasonicate for 10 to 40 minutes in a vacuum environment until they are uniform, and obtain a first slurry, wherein the vacuum degree of the vacuum environment is 0.06 to 0.08 KPA, the rotation speed of the stirring is 1000 to 3000 r / min, the revolution speed is 30 to 60 r / min, and the ultrasonic frequency of the ultrasound is 5 to 8 kHz.
[0026] In the above technical solution, the method for preparing the second slurry specifically comprises the following steps:
[0027] S1, mixing small-pore porous alumina, water and a dispersant, and stirring at a rotation speed of 1000 to 3000 r / min and a revolution speed of 30 to 50 r / min for 10 to 30 minutes until the mixture is uniform, to obtain a second solution;
[0028] S2, mixing the second solution and the adhesive, stirring and ultrasonicating for 10 to 40 minutes in a vacuum environment until they are uniform, to obtain a second slurry, wherein the vacuum degree of the vacuum environment is 0.06 to 0.08 KPA, the rotation speed of the stirring is 1000 to 3000 r / min, the revolution speed is 30 to 60 r / min, and the ultrasonic frequency of the ultrasonication is 5 to 8 kHz.
[0029] In the above technical solution, the dispersant is ammonium polyacrylate, and the adhesive is an acrylate copolymer solution.
[0030] In the above technical solution, the content of the acrylate copolymer in the acrylate copolymer solution is 20 to 40 wt %.
[0031] The application of large-pore porous alumina and small-pore porous alumina synergistically improving the ionic conductivity, liquid absorption rate, liquid retention rate, tensile strength and / or breakdown voltage of the separator.
[0032] Application of large-pore porous alumina and small-pore porous alumina to synergistically reduce the shrinkage rate of the diaphragm.
[0033] In the above technical solution, the diaphragm is a layered structure, which includes: a base membrane, a first coating and a second coating, the first coating and the second coating are located on the same side of the base membrane, the first coating is connected to one side of the base membrane, the second coating is connected to the first coating, the large-pore porous alumina is located in the first coating, and the small-pore porous alumina is located in the second coating. In terms of mass fractions, the ratio of the large-pore porous alumina in the first coating to the small-pore porous alumina in the second coating is (10 to 30): (10 to 30).
[0034] Compared with the prior art, the present invention has the following beneficial effects:
[0035] 1. Optimization of pore size distribution: By designing pore size distributions of different sizes, the flow of electrolyte and the transport of ions can be effectively controlled. Larger pore sizes facilitate rapid transport of electrolytes, thereby improving ion conductivity, while smaller pore sizes prevent short circuits and improve the mechanical strength and heat resistance of the separator;
[0036] 2. Construction of double-layer structure: The double-layer structure design is adopted, and the two layers of coating have different pore sizes, thus forming a gradient pore size structure. This structure can achieve the gradual adaptation of ions during the battery charging and discharging process and reduce the migration energy barrier. DETAILED DESCRIPTION
[0037] The technical solution of the present invention is further described below in conjunction with specific embodiments.
[0038] Small-pore porous alumina (powder), large-pore porous alumina (powder): Suzhou Jinyi New Material Technology Co., Ltd.;
[0039] Acrylate copolymer solution: Baoding Lucky Imaging Material Technology Co., Ltd.;
[0040] Ammonium polyacrylate: Shanghai Sanrui Polymer Materials Technology Co., Ltd.
[0041] Double planetary mixer: XFZH-30L.
[0042] In the following examples and comparative examples, the particle size of the small-pore porous alumina is D50=0.325 μm, D90=0.812 μm, the pore size of the small-pore porous alumina is 11.2 nm, and the specific surface area of the small-pore porous alumina is 16.9 m 2 / g.
[0043] In the following examples and comparative examples, the particle size of the large-pore porous alumina is D50=0.679 μm, D90=1.516 μm, the pore size of the large-pore porous alumina is 60.2 nm, and the specific surface area of the large-pore porous alumina is 31.1 m 2 / g.
[0044] In the following embodiments, water is pure water.
[0045] In the following implementation, the base film is a PE film, and the thickness of the PE film is 9 μm.
[0046] Ionic conductivity: The test temperature is 25°C and the relative humidity is 60%.
[0047] Example 1
[0048] A method for preparing a lithium battery separator with a gradient pore structure comprises: coating a first slurry containing large-pore porous alumina on one side of a base film at a speed of 15 m / min, pulling the slurry into a drying device via a pulling roller, and drying the slurry at 50°C for 1 min to obtain a first coating layer with a thickness of 2.1 μm on one side of the base film; coating a second slurry containing small-pore porous alumina on the surface of the first coating layer at a speed of 15 m / min, pulling the slurry into a drying device via a pulling roller, and drying the slurry at 50°C for 1 min to obtain a second coating layer with a thickness of 1 μm on the first coating layer to obtain a lithium battery separator with a gradient pore structure, wherein the porosity of the first coating layer is 41.2% and the porosity of the second coating layer is 33.5%.
[0049] The method for preparing the first slurry comprises the following steps:
[0050] Step 1, mixing large-pore porous alumina, water and a dispersant in a double planetary mixer, stirring for 10 minutes at a rotation speed of 1000 r / min and a revolution speed of 30 r / min until uniform, to obtain a first solution, wherein the dispersant is ammonium polyacrylate;
[0051] Step 2, adding an adhesive to the first solution, stirring and ultrasonicating for 10 minutes in a double planetary mixer with ultrasonic oscillation function under a vacuum environment until uniform, to obtain a first slurry, wherein the vacuum degree of the vacuum environment is 0.06KPA, the rotation speed of the stirring is 1500r / min, the revolution speed is 30r / min, the ultrasonic frequency of the ultrasound is 5kHz, and the ratio of large-pore porous alumina, water in the first slurry, adhesive in the first slurry and dispersant in the first slurry is 11:83.5:5:0.5 by mass, and the adhesive is an acrylate copolymer solution (the content of acrylate copolymer in the acrylate copolymer solution is 20wt%, and the acrylate copolymer is copolymerized by acrylic acid and acrylamide).
[0052] The method for preparing the second slurry comprises the following steps:
[0053] S1, mixing small-pore porous alumina, water and a dispersant in a double planetary mixer, stirring for 10 minutes at a rotation speed of 1000 r / min and a revolution speed of 30 r / min until uniform, to obtain a second solution, wherein the dispersant is ammonium polyacrylate;
[0054] S2, adding an adhesive to the second solution, stirring and ultrasonicating for 10 minutes in a double planetary mixer with ultrasonic oscillation function under vacuum environment until uniform, to obtain a second slurry, wherein the vacuum degree of the vacuum environment is 0.06KPA, the rotation speed of the stirring is 1500r / min, the revolution speed is 30r / min, the ultrasonic frequency of the ultrasound is 5kHz, and the ratio of small-pore porous alumina, water in the second slurry, adhesive in the second slurry and dispersant in the second slurry is 11:83.5:5:0.5 by mass, and the adhesive is an acrylate copolymer solution (the content of acrylate copolymer in the acrylate copolymer solution is 20wt%, and the acrylate copolymer is copolymerized by acrylic acid and acrylamide).
[0055] The test data of the lithium battery separator with gradient pore structure prepared in Example 1 are as follows:
[0056]
[0057]
[0058] Example 2
[0059] A method for preparing a lithium battery separator with a gradient pore structure comprises: coating a first slurry containing large-pore porous alumina on one side of a base film at a speed of 20 m / min, pulling the slurry into a drying device via a pulling roller, and drying the slurry at 40°C for 2 min to obtain a first coating layer with a thickness of 2.2 μm on one side of the base film; coating a second slurry containing small-pore porous alumina on the surface of the first coating layer at a speed of 20 m / min, pulling the slurry into a drying device via a pulling roller, and drying the slurry at 40°C for 2 min to obtain a second coating layer with a thickness of 1.1 μm on the first coating layer to obtain a lithium battery separator with a gradient pore structure, wherein the porosity of the first coating layer is 45.3% and the porosity of the second coating layer is 35.6%.
[0060] The method for preparing the first slurry comprises the following steps:
[0061] Step 1, mixing large-pore porous alumina, water and a dispersant in a double planetary mixer, stirring at a rotation speed of 2000 r / min and a revolution speed of 40 r / min for 20 minutes until uniform, to obtain a first solution, wherein the dispersant is ammonium polyacrylate;
[0062] Step 2, adding an adhesive to the first solution, stirring and ultrasonicating for 20 minutes in a double planetary mixer with ultrasonic oscillation function under a vacuum environment until uniform, to obtain a first slurry, wherein the vacuum degree of the vacuum environment is 0.07KPA, the rotation speed of the stirring is 2000r / min, the revolution speed is 40r / min, the ultrasonic frequency of the ultrasound is 6kHz, and the ratio of large-pore porous alumina, water in the first slurry, adhesive in the first slurry and dispersant in the first slurry is 20:71.2:8:0.8 by mass, and the adhesive is an acrylate copolymer solution (the content of acrylate copolymer in the acrylate copolymer solution is 20wt%, and the acrylate copolymer is copolymerized by acrylic acid and acrylamide).
[0063] The method for preparing the second slurry comprises the following steps:
[0064] S1, mixing small-pore porous alumina, water and a dispersant in a double planetary mixer, stirring at a rotation speed of 2000 r / min and a revolution speed of 40 r / min for 20 min until uniform, to obtain a second solution, wherein the dispersant is ammonium polyacrylate;
[0065] S2, adding an adhesive to the second solution, stirring and ultrasonicating for 20 minutes in a double planetary mixer with ultrasonic oscillation function under vacuum environment until uniform, to obtain a second slurry, wherein the vacuum degree of the vacuum environment is 0.07KPA, the rotation speed of the stirring is 2000r / min, the revolution speed is 40r / min, the ultrasonic frequency of the ultrasound is 6kHz, and the ratio of small-pore porous alumina, water in the second slurry, adhesive in the second slurry and dispersant in the second slurry is 20:71.2:8:0.8 by mass, and the adhesive is an acrylate copolymer solution (the content of acrylate copolymer in the acrylate copolymer solution is 20wt%, and the acrylate copolymer is copolymerized by acrylic acid and acrylamide).
[0066] The test data of the lithium battery separator with gradient pore structure prepared in Example 2 are as follows:
[0067]
[0068] Example 3
[0069] A method for preparing a lithium battery separator with a gradient pore structure comprises: coating a first slurry containing large-pore porous alumina on one side of a base film at a speed of 30 m / min, pulling the slurry into a drying device via a pulling roller, and drying the slurry at 30°C for 4 min to obtain a first coating layer with a thickness of 2.2 m on one side of the base film; coating a second slurry containing small-pore porous alumina on the surface of the first coating layer at a speed of 30 m / min, pulling the slurry into a drying device via a pulling roller, and drying the slurry at 30°C for 4 min to obtain a second coating layer with a thickness of 1 μm on the first coating layer to obtain a lithium battery separator with a gradient pore structure, wherein the porosity of the first coating layer is 48.2% and the porosity of the second coating layer is 39.5%.
[0070] The method for preparing the first slurry comprises the following steps:
[0071] Step 1, mixing large-pore porous alumina, water and a dispersant in a double planetary mixer, stirring at a rotation speed of 3000 r / min and a revolution speed of 50 r / min for 30 minutes until uniform, to obtain a first solution, wherein the dispersant is ammonium polyacrylate;
[0072] Step 2, adding an adhesive to the first solution, stirring and ultrasonicating for 20 minutes in a double planetary mixer with ultrasonic oscillation function under a vacuum environment until uniform, to obtain a first slurry, wherein the vacuum degree of the vacuum environment is 0.08KPA, the rotation speed of the stirring is 3000r / min, the revolution speed is 60r / min, the ultrasonic frequency of the ultrasound is 8kHz, and the ratio of large-pore porous alumina, water in the first slurry, adhesive in the first slurry and dispersant in the first slurry is 30:59:10:1 by mass, and the adhesive is an acrylate copolymer solution (the content of acrylate copolymer in the acrylate copolymer solution is 20wt%, and the acrylate copolymer is copolymerized by acrylic acid and acrylamide).
[0073] The method for preparing the second slurry comprises the following steps:
[0074] S1, mixing small-pore porous alumina, water and a dispersant in a double planetary mixer, stirring at a rotation speed of 3000 r / min and a revolution speed of 50 r / min for 30 min until uniform, to obtain a second solution, wherein the dispersant is ammonium polyacrylate;
[0075] S2, adding an adhesive to the second solution, stirring and ultrasonicating for 20 minutes in a double planetary mixer with ultrasonic oscillation function under vacuum environment until uniform, to obtain a second slurry, wherein the vacuum degree of the vacuum environment is 0.08KPA, the rotation speed of the stirring is 3000r / min, the revolution speed is 60r / min, the ultrasonic frequency of the ultrasound is 8kHz, and the ratio of small-pore porous alumina, water in the second slurry, adhesive in the second slurry and dispersant in the second slurry is 30:59:10:1 by mass, and the adhesive is an acrylate copolymer solution (the content of acrylate copolymer in the acrylate copolymer solution is 20wt%, and the acrylate copolymer is copolymerized by acrylic acid and acrylamide).
[0076] The test data of the lithium battery separator with gradient pore structure prepared in Example 3 are as follows:
[0077]
[0078]
[0079] Comparative Example 1
[0080] A method for preparing a diaphragm comprises the following steps:
[0081] Step 1, mixing small-pore porous alumina, water and a dispersant in a double planetary mixer, stirring at a rotation speed of 3000 r / min and a revolution speed of 45 r / min for 30 minutes until uniform, to obtain a second solution, wherein the dispersant is ammonium polyacrylate;
[0082] Step 2, adding an adhesive to the second solution, stirring and ultrasonicating for 30 minutes in a double planetary mixer with an ultrasonic oscillation function in a vacuum environment until uniform, to obtain a slurry, wherein the vacuum degree of the vacuum environment is 0.07KPA, the rotation speed of the stirring is 2500r / min, the revolution speed is 50r / min, the ultrasonic frequency of the ultrasound is 6kHz, and the ratio of small-pore porous alumina, water, adhesive and dispersant is 20:72.2:7:0.8 by mass, and the adhesive is an acrylate copolymer solution (the content of the acrylate copolymer in the acrylate copolymer solution is 20wt%, and the acrylate copolymer is copolymerized by acrylic acid and acrylamide);
[0083] Step 3, place the base film on a coating machine containing the slurry prepared in step 2, coat the slurry on one side of the base film at a speed of 20m / min, pull it into a drying device through a traction roller, and dry it at 45°C for 2min to obtain a coating on one side of the base film, thereby obtaining the diaphragm of comparative example 1.
[0084] The parameters of the diaphragm prepared in Comparative Example 1 are as follows:
[0085]
[0086] Comparative Example 2
[0087] A method for preparing a diaphragm comprises the following steps:
[0088] Step 1, mixing large-pore porous alumina, water and a dispersant in a double planetary mixer, stirring at a rotation speed of 3000 r / min and a revolution speed of 40 r / min for 30 minutes until uniform, to obtain a first solution, wherein the dispersant is ammonium polyacrylate;
[0089] Step 2, adding an adhesive to the first solution, stirring and ultrasonicating for 30 minutes in a double planetary mixer with an ultrasonic oscillation function in a vacuum environment until uniform, to obtain a slurry, wherein the vacuum degree of the vacuum environment is 0.06KPA, the rotation speed of the stirring is 3000r / min, the revolution speed is 40r / min, the ultrasonic frequency of the ultrasound is 5kHz, and the ratio of large-pore porous alumina, water, adhesive and dispersant is 20:71.5:8:0.5 by mass, and the adhesive is an acrylate copolymer solution (the content of the acrylate copolymer in the acrylate copolymer solution is 20wt%, and the acrylate copolymer is copolymerized by acrylic acid and acrylamide);
[0090] Step 3, place the base film on a coating machine containing the slurry prepared in step 2, coat the slurry on one side of the base film at a speed of 20m / min, pull it into a drying device through a traction roller, and dry it at 50°C for 1min to obtain a coating on one side of the base film, thereby obtaining the diaphragm of comparative example 2.
[0091] The parameters of the diaphragm prepared in Comparative Example 2 are as follows:
[0092]
[0093] Comparative Example 3
[0094] A method for preparing a heat-resistant aluminum oxide lithium battery diaphragm comprises the following steps:
[0095] Step 1, conventional alumina (D10 = 0.218 μm, D50 = 0.502 μm, D90 = 1.556 μm, non-porous alumina), water and dispersant are mixed in a double planetary mixer, first stirred at a rotation speed of 3000 r / min and a revolution speed of 50 r / min for 30 min, then ultrasonicated at a frequency of 6 kHz for 20 min, an adhesive is added, and stirred and ultrasonicated for 20 min in a double planetary mixer with an ultrasonic oscillation function under a vacuum environment (the vacuum degree of the vacuum environment is 0.06 KPA, the rotation speed of the stirring is 2000 r / min, the revolution speed is 40 r / min, and the ultrasonic frequency of the ultrasonication is 6 kHz) to obtain a slurry, wherein the adhesive and the dispersant are the same as those used in Example 1, and the ratio of conventional alumina, water, adhesive and dispersant is 20:71.2:8:0.8 by mass;
[0096] Step 2, place the base film on a coating machine containing the slurry prepared in step 1, coat the slurry on one side of the base film at a speed of 20m / min, pull it into a drying device through a traction roller, and dry it at 45°C for 2min to obtain a coating on one side of the base film to obtain a heat-resistant alumina lithium battery separator.
[0097] The heat-resistant aluminum oxide lithium battery diaphragm prepared in Comparative Example 3 was tested, and the test results are shown in the following table:
[0098]
[0099] Comparative Example 4
[0100] A method for preparing a lithium battery separator with a gradient pore structure, comprising: coating a second slurry containing small-pore porous alumina (the same as the second slurry in Example 1) on one side of a base film at a speed of 15 m / min, pulling the second slurry into a drying device via a pulling roller, and drying it at 50°C for 1 min to obtain a 2.1 μm thick A coating on one side of the base film; coating a first slurry containing large-pore porous alumina (the same as the first slurry in Example 1) on one side of an A coating at a speed of 15 m / min, pulling the second slurry into a drying device via a pulling roller, and drying it at 50°C for 1 min to obtain a 1 μm thick B coating on the A coating to obtain a lithium battery separator with a gradient pore structure, wherein the porosity of the A coating is 35.2%, and the porosity of the B coating is 40.3%.
[0101] The parameters of the diaphragm prepared in Comparative Example 4 are as follows:
[0102]
[0103] In summary, the present invention adopts a double coating structure design, and the two coatings have different pore sizes, thereby forming a gradient pore size structure. The pore size gradient is designed so that the ions can gradually adapt to the environment of different pore sizes when entering the electrode material. This design can enable the ions to undergo a smooth transition during the migration process. This structure can achieve the gradual adaptation of ions and reduce the migration energy barrier during the battery charging and discharging process. Under fast charging conditions, the gradient pore structure can make lithium ions more evenly attached to the negative electrode, which can effectively inhibit the generation of lithium dendrites. Larger pore sizes provide more space for ion diffusion and reduce the diffusion restriction of ions at the interface between the electrode and the electrolyte. As the pore size decreases, the movement of ions in the pores will be subject to certain constraints, but this gradual adaptation helps to improve the overall ionic conductivity. The rich pore structure of small-pore porous alumina and large-pore porous alumina can make the diaphragm have a good liquid absorption and retention rate.
[0104] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.
Claims
1. A lithium battery separator having a gradient pore structure, characterized in that: The invention is a layered structure, which comprises: a base film, a first coating and a second coating, wherein the first coating and the second coating are located on the same side of the base film, the first coating is connected to one side of the base film, the second coating is connected to the first coating, the porosity of the first coating is 40-50%, the porosity of the second coating is 30-40%, the first coating comprises: large-pore porous alumina, the pore size of the large-pore porous alumina is 50-100 nm, the second coating comprises: small-pore porous alumina, the pore size of the small-pore porous alumina is 10-20 nm, and the ratio of the large-pore porous alumina in the first coating to the small-pore porous alumina in the second coating is (10-30):(10-30) by mass.
2. The lithium battery separator with a gradient pore structure according to claim 1, characterized in that: The particle size of the large-pore porous alumina is D50=0.6-0.8 μm, D90=1.4-1.6 μm, and the specific surface area of the large-pore porous alumina is 30-40 m 2 / g.
3. The lithium battery separator with a gradient pore structure according to claim 1, characterized in that: The particle size of the small-pore porous alumina is D50=0.3-0.5 μm, D90=0.8-1.2 μm, and the specific surface area of the small-pore porous alumina is 10-20 m 2 / g.
4. The lithium battery separator with a gradient pore structure according to claim 1, characterized in that: The thickness of the first coating layer is 1 to 2.5 μm, and the thickness of the second coating layer is 1 to 2.5 μm.
5. The method for preparing a lithium battery separator having a gradient pore structure according to any one of claims 1 to 4, characterized in that: include: A first slurry containing large-pore porous alumina is coated on a base membrane and dried to obtain a first coating on the base membrane; a second slurry containing small-pore porous alumina is coated on the surface of the first coating and dried to obtain a second coating on the first coating to obtain a lithium battery separator with a gradient pore structure.
6. The preparation method according to claim 5, characterized in that: The first slurry includes: large-pore porous alumina, water, an adhesive and a dispersant. In terms of mass percentage, the ratio of large-pore porous alumina, water in the first slurry, the adhesive in the first slurry and the dispersant in the first slurry is (10-30): (50-90): (5-10): (0.5-1).
7. The preparation method according to claim 5, characterized in that: The second slurry includes: small-pore porous alumina, water, adhesive and dispersant. In terms of mass percentage, the ratio of small-pore porous alumina, water in the second slurry, adhesive in the second slurry and dispersant in the second slurry is (10-30): (50-90): (5-10): (0.5-1).
8. The preparation method according to claim 5, characterized in that: The dispersant is ammonium polyacrylate, and the adhesive is an acrylate copolymer solution.
9. Application of large-pore porous alumina and small-pore porous alumina to synergistically improve the ionic conductivity, liquid absorption rate, liquid retention rate, tensile strength and / or breakdown voltage of the separator.
10. The application of large-pore porous alumina and small-pore porous alumina to synergistically reduce the shrinkage rate of the diaphragm.
Citation Information
Patent Citations
Anode of lithium-ion battery and lithium-ion battery prepared from same
CN105185938A
Diaphragm, preparation method of diaphragm and battery
CN117895187A
Separator and electrochemical device comprising same
US20180277815A1
Separator for secondary battery, manufacturing method therefor, and secondary battery having separator
WO2022015026A1
Separator for sodium battery, secondary battery, and electrical apparatus
WO2024227368A1
Cited By
Gradient pore diaphragm dynamic roll forming device and method for silicon-based negative electrode
CN120824512A
A dynamic roll forming device and method for gradient porous separator for silicon-based negative electrode
CN120824512B
Separator, and electrochemical device and electronic device including same
CN121261060A
Separator, and electrochemical device and electronic device including same
CN121261061A
Battery diaphragm as well as preparation method and application thereof
CN121367027A